City sense and city design - Lynch, Kevin (Cambridge, Mass. : MIT Press, 1995)
The essays in part I focus on the premises of Lynch's work: his novel reading of large-scale built environments and the notion that the design of an urban landscape should be as meaningful and intimate as the natural landscape. In part II, excerpts from Lynch's travel journals reveal his early ideas on how people perceive and interpret their surroundings$1 (Bideas that culminated in his seminal work, The Image of the City. This part of the book also presents Lynch's experiments with children and his assessment of environmental-perception research. The examples of both small-scale and large-scale analysis of visual form in part III are followed by three parts on city design. These include Lynch's more theoretical works on complex planning decisions involving both functional (spatial and structural organization) and normative (how the city works in human terms) approaches, articles discussing the principles that guided Lynch's teaching and practice of city design, and descriptions of Lynch's own projects in the Boston area and elsewhere. The book concludes with essays written late in Lynch's career, fantasy pieces describing utopias and offering new design freedoms and scenarios warning of horrifying "cacotopias."s
I. The form of cities -- II. Experiencing Cities -- III. Analysis of visual form -- IV. City Design: Theory -- V. City Design: Education and Practice -- VI. City Design: Projects -- VII. Utopias and Cacotopias.
First MIT Press paperback edition, 1995
Keywords: CITY PLANNING; URBAN DESIGN